Krisen, Kritik und Sexualnot Die «Nacherziehung» männlicher Jugendlicher in der Anstalt Aarburg (1893-1981) - Heiniger, Kevin (Chronos Verlag, 2016)
Crises, Criticism, and Sexual Deprivation The «Nacherziehung» (remedial upbringing) of male youth at the Aarburg facility, 1893-1981 The juvenile detention center Aarburg, founded in 1893, adhered superficially to an objective of separating juvenile offenders from adult offenders. From the beginning, however, roughly half of the inmates were institutionalized there in order to provide them with administrative maintenance. Power struggles soon after the institution opened, accusations of maltreatment and the suicide of two youths in the First World War era, the widely publicized critique of 1936 and the finally the "Heimkampagne" of 1970 are the focuses of this book. Source-based case studies sketch a nuanced picture of the daily life of the Aarburg institution across diverse decades, and the imponderability of interpersonal relations within the permanent emergency condition of a "total" institution. The author also devotes attention to the effects of sexual repression on the young inmates, which was not mentioned or addressed in official reports, making all the more striking, examples of this found within the archival sources analyzed here for the first time. The book offers insights into the quotidian experience of the inmates across the 20th century and also demonstrates the evolution of child-rearing techniques used on male juveniles.